2014
DOI: 10.1063/1.4902338
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic pressure measurement in pressure vessels

Abstract: Based on the reflected longitudinal wave, a new non-intrusive method for pressure measurement is proposed. The acoustoelastic theory and the thin-shell theory are introduced to develop the pressure measurement model in cylindrical pressure vessels. And a pressure measurement system is constructed to evaluate the effectiveness of the proposed method. The pressure measurement is implemented by measuring the travel-time change between two received ultrasonic sensors. The experimental results verify the feasibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The relationships between the pressure and propagation time of different ultrasonic waves have already been studied in our previous works. For example, Rayleigh wave has been discussed in [ 6 ], the L CR wave in [ 6 ], and the reflected longitudinal wave in [ 7 ]. However, the accuracy of pressure measurement depends heavily on the accuracy of the propagation time measurement, which can be affected by multiple factors, including noise, temperature, etc.…”
Section: Pressure Measurement Methods Based On L Cr mentioning
confidence: 99%
See 2 more Smart Citations
“…The relationships between the pressure and propagation time of different ultrasonic waves have already been studied in our previous works. For example, Rayleigh wave has been discussed in [ 6 ], the L CR wave in [ 6 ], and the reflected longitudinal wave in [ 7 ]. However, the accuracy of pressure measurement depends heavily on the accuracy of the propagation time measurement, which can be affected by multiple factors, including noise, temperature, etc.…”
Section: Pressure Measurement Methods Based On L Cr mentioning
confidence: 99%
“…There is another approach to measure the pressure—non-invasive approaches [ 1 ]. There are several proposed methods of this approach, such as the strain gauge method [ 2 ], the capacitor method [ 3 ], and the ultrasonic method [ 4 , 5 , 6 , 7 ]. These methods can solve some problems, but there is still room for improvement in terms of the accuracy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3, the experiment system consists of seven parts: pressure test pump, pressure vessel, biochemical incubator, ultrasonic probes, ultrasonic exciting circuit, high-speed acquisition system and computer. In order to reduce the influence of temperature, the dual-receivers mode was adopted [14], which means three probes are arranged in the axial direction of the vessel, including one transmitter (T) and two receivers (R1, R2).…”
Section: Experiments Systemmentioning
confidence: 99%
“…Zhang et al [12,13] have analyzed the acoustoelastic effect in the thin-walled vessels and proposed a method of pressure measurement based on the observation that the propagation velocity of the ultrasonic wave is usually influenced by the stress on the vessel wall. In our previous research [14], we identified that the surface wave and the critically refracted longitudinal wave (L CR wave) are all susceptible to the roughness of the vessel's outer surface. Instead of measuring L CR wave, we concluded that the signal-to-noise ratio (SNR) and the sensitivity in the measurement can be significantly improved by taking the reflected longitudinal waves into the measurement.…”
Section: Introductionmentioning
confidence: 99%